2007
DOI: 10.1111/j.1447-0756.2007.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Kampo therapy for premenstrual syndrome: Efficacy of Kamishoyosan quantified using the second derivative of the fingertip photoplethysmogram

Abstract: The improvement of PMS symptoms as a result of using Kamishoyosan was quantified by means of SDPTG and the self-assessment questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Despite the differences in experimental designs and conditions as well as an index of the autonomic nervous system, these earlier investigations [26,[31][32][33][34] support our findings, indicating that the occurrence of premenstrual symptomatology could be attributable to an altered functioning of the autonomic nervous system in the symptomatic late luteal phase. The findings of PMDD from the present study together with Landen et al [26] and Girdler et al [34] indicate sympathovagal activity was altered even in the follicular phase.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Despite the differences in experimental designs and conditions as well as an index of the autonomic nervous system, these earlier investigations [26,[31][32][33][34] support our findings, indicating that the occurrence of premenstrual symptomatology could be attributable to an altered functioning of the autonomic nervous system in the symptomatic late luteal phase. The findings of PMDD from the present study together with Landen et al [26] and Girdler et al [34] indicate sympathovagal activity was altered even in the follicular phase.…”
Section: Discussionsupporting
confidence: 78%
“…Kondo et al [31] measured the coefficient of variation of R-R interval during the Examples of ECG R-R interval changes and the corresponding power spectra during the follicular and late luteal phase for subjects in the Control, PMS, and PMDD groups menstrual cycle and demonstrated that the parasympathetic nerve activity was lower in the late luteal phase than in the follicular phase in women with PMS. A recent clinical study by Kimura et al [32] has applied noninvasive pulse wave analysis to assess the peripheral autonomic reaction as well as arterial elasticity properties and suggested that Kampo therapy could induce vascular rejuvenation, an indication of improvement of autonomic nervous disturbance in PMS patients, while significantly improving premenstrual discomfort. We have utilized the venous oxygenation index (VOI) via the principle of nearinfrared spectroscopy to evaluate peripheral blood circulation and demonstrated that the VOI significantly decreased in women with PMS [33].…”
Section: Discussionmentioning
confidence: 99%
“…The second commonly prescribed herbal formula, Jia-WeiXiao-Yao-San, has been used for thousand of years to treat women's disorder ranging from menstrual problems, infertility to menopausal syndromes (Scheid et al, 2009). In addition it has been reported as an effective treatment for premenstrual syndrome and various mood disorders, and possess anxiolytic effects (Kimura et al, 2007;Wang et al, 2009;Zhang et al, 2007). These effects of Jia-Wei-Xiao-Yao-San are especially favorable as it has recently been demonstrated that women are prone to mood disorders and anxiety (Steel et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…For this purpose, we used the computer-aided kampo database known as Tokyo Women's Medical University Oriental Medicine Research Active Support System (TOMRASS), which accumulates patient-based evaluations covering a wide range of complaints, symptoms, and conditions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%